2016
DOI: 10.1111/add.13638
|View full text |Cite
|
Sign up to set email alerts
|

Do never smokers make up an increasing share of snus users as cigarette smoking declines? Changes in smoking status among male snus users in Norway 2003–15

Abstract: AimsTo examine how the relative size of six groups of male ever snus users (current and former users of snus who were current, former or never cigarette smokers) varied over time in Norway, and how these groups differ with regard to important measures of tobacco behaviour.DesignRepeated cross‐sectional nationally representative surveys of tobacco use. The association between survey year and the six categories of ever snus use was examined using cross‐tabulation and multinomial logistic regression. Differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
(52 reference statements)
2
15
0
Order By: Relevance
“…Our study has shown that the majority of snus users (at least 75%)—whether current or former – were current or former smokers (ever smokers). This finding is consistent with Norwegian studies based on other data sets [ 36 38 ]. However, the novel finding from our study is that daily smokers and former daily smokers were more likely to use flavoured snus products compared to snus users without any prior history of smoking.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study has shown that the majority of snus users (at least 75%)—whether current or former – were current or former smokers (ever smokers). This finding is consistent with Norwegian studies based on other data sets [ 36 38 ]. However, the novel finding from our study is that daily smokers and former daily smokers were more likely to use flavoured snus products compared to snus users without any prior history of smoking.…”
Section: Discussionsupporting
confidence: 93%
“…In this segment of potential snus users, susceptibility to flavoured products would contribute negatively to public health. However, according to our study-and several others-the largest reservoir of potential snus users have until now been smokers-not never smokers [36][37][38].…”
Section: Risk-use Equilibriumsupporting
confidence: 55%
“…Up until now, studies have demonstrated that the largest reservoir of potential snus users has been smokers, and that use among never-smokers is small [ 43 ]. Based on current knowledge of the a) absolute risk of snus use relative to non-use, b) the relative risk of snus relative to smoking, and c) how the population of snus users is made up of never-smokers and smokers (the user configuration), dissemination of information to correct misconceptions of relative risk will probably result in a net gain to public health.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, 20% of males and 10% of females were ever snus users . Former smokers constitute the majority of current Norwegian snus users .…”
Section: Introductionmentioning
confidence: 99%